1996
DOI: 10.1083/jcb.133.3.647
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglian-mediated cell adhesion induces assembly of the membrane skeleton at cell contact sites.

Abstract: Abstract. The protein ankyrin links integral membrane proteins to the spectrin-based membrane skeleton. Ankyrin is often concentrated within restricted membrane domains of polarized epithelia and neurons, but the mechanisms responsible for membrane targeting and its segregation within a continuous lipid bilayer remain unexplained. We provide evidence that neuroglian, a cell adhesion molecule related to L1 and neurofascin, can transmit positional information directly to ankyrin and thereby polarize its distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 42 publications
7
119
1
Order By: Relevance
“…Following homophilic binding, CAMs of the L1 family transduce signals resulting in the recruitment of ankyrin and spectrin to points of cell-cell contact (13)(14)(15)(16)(17). Drosophila S2 cells are a classic model system in which potential CAMs have been tested for these properties (14,27).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following homophilic binding, CAMs of the L1 family transduce signals resulting in the recruitment of ankyrin and spectrin to points of cell-cell contact (13)(14)(15)(16)(17). Drosophila S2 cells are a classic model system in which potential CAMs have been tested for these properties (14,27).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that sodium channel ␤ subunits function as CAMs. CAMs of the L1 family also bind directly to cytoskeletal elements such as ankyrin (12,13,(15)(16)(17). Sodium channels have been shown to colocalize with ankyrin G and spectrin at axon initial segments and nodes of Ranvier, and there is some evidence to show that sodium channels bind ankyrin directly in vitro (18 -22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has, however, been used successfully to study the interactions of the extracellular domains of transmembrane proteins (31,32). Numerous questions have been raised as to whether two-hybrid systems are applicable to the analysis of interactions between extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Fas2 directly binds Dlg (Goodman et al, 1997). Third, molecular interactions between Nrg, Ankyrin, and Spectrin (Dubreuil et al, 1996;Hortsch et al, 1998) suggest a manner for Nrg to be linked to Fas2-Dlg through membrane protein 4.1 (Fig. 1B).…”
Section: Fas2 Dlg Lgl and Nrg Function Together To Suppress Invasionmentioning
confidence: 99%